Coaching supervision groups : resourcing in practitioners - Birch, Jo, 1957- (Abingdon, Oxon ; New York, NY : Routledge, 2022)
Written by experienced coaching supervisors, this book offers a kaleidoscope of wisdom drawn from a complex professional field. Theoretical concepts, practitioner research, models and techniques are brought alive here through the lived experience of the authors. As coaching supervisors continue to develop their practice, those wishing to extend their skills into group work step into a new context which stretches and strengthens their own learning, as well as that of supervisees, in this mutual, intentional learning environment. Coaching supervisors are encouraged to begin with the inner journey, developing their own knowledge as each chapter offers a new perspective, enabling readers to gain a philosophical understanding of the process, which will guide them on their journey through the unpredictable terrain of group work. Coaches, mentors and other practitioners looking for a Supervision Group experience will gain insights into the range of opportunities available, opening myriad possibilities for furthering personal and professional learning.
"Written by experienced coaching supervisors, this book offers a kaleidoscope of wisdom drawn from a complex professional field. Theoretical concepts, practitioner research, models and techniques are brought alive here through the lived experience of the authors. As Coaching Supervisors continue to develop their practice, those wishing to extend their skills into group work step into a new context which stretches and strengthens their own learning, as well as that of supervisees, in this mutual, intentional learning environment. Coaching supervisors are encouraged to begin with the inner journey, developing their own knowledge as each chapter offers a new perspective, enabling readers to gain a philosophical understanding of the process, which will guide them on their journey through the unpredictable terrain of group work. Coaches, mentors and other practitioners looking for a Supervision Group experience will gain insights into the range of opportunities available, opening myriad possibilities for furthering personal and professional learning"-- Provided by publisher.
Keywords: Personal coaching; Counselors -- Supervision of; PSYCHOLOGY / Mental Health